2000
DOI: 10.1177/135245850000600213
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue in multiple sclerosis: relationship to depression, disability, and disease pattern

Abstract: In order to investigate the associations between fatigue and depression, disability, and disease subtype, 207 individuals with clinically definite Multiple Sclerosis (MS) were administered the Fatigue Severity Scale and the Zung Self-rating Depression Scale during a regular clinic appointment. Their current level of disability was established using the Expanded Disability Status Scale. Fatigue and depression were highly correlated (r=0.58), even when the depression measure was corrected for items overlapping w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
112
2
4

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 208 publications
(130 citation statements)
references
References 17 publications
11
112
2
4
Order By: Relevance
“…Mood has been characterized as a contributor to MS fatigue in many studies. [5][6][7] However, our findings suggest that mood may affect the perception of fatigue more than its cognitive correlates in MS. This hypothesis is supported by a recent study showing that MS patients' self-rankings on the Beck Depression Inventory Fast Screen were moderately correlated with rankings on the Fatigue Severity Scale, but not with cognitive results from formal neuropsychological testing.…”
Section: Discussioncontrasting
confidence: 50%
See 2 more Smart Citations
“…Mood has been characterized as a contributor to MS fatigue in many studies. [5][6][7] However, our findings suggest that mood may affect the perception of fatigue more than its cognitive correlates in MS. This hypothesis is supported by a recent study showing that MS patients' self-rankings on the Beck Depression Inventory Fast Screen were moderately correlated with rankings on the Fatigue Severity Scale, but not with cognitive results from formal neuropsychological testing.…”
Section: Discussioncontrasting
confidence: 50%
“…Mood has been demonstrated in previous research to be correlated with MS fatigue, but did not significantly affect reaction times in this study. [4][5]7 The PVT can be influenced by demographic factors that have not been consistently linked to MS-related fatigue. For example, in other studies age has been shown to affect PVT performance, and in this study, gender was a significant contributor.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fatigue in MS may be related to impaired interactions among functionally related cortical and subcortical areas, it could be a side effect of depression, or both. 15,31,32 MS-related cognitive dysfunction could be a function of fatigue, central inflammation, neurodegeneration, neuroendocrine dysregulation, and/or depression. 33 This study is the first to document moderate correlations between measurements of fatigue and cognitive function at baseline and during natalizumab treatment.…”
Section: Discussionmentioning
confidence: 99%
“…14 Fatigue and cognitive deficits are associated with disability. 15,16 Although fatigue and cognition are not explicitly captured by the Expanded Disability Status Scale (EDSS), a reduction in sustained disability progression as measured by the EDSS is seen with natalizumab as compared with placebo. 13 Here we report findings from the Evaluation of Natalizumab for thE Relief of MS Associated FatiGue (ENER-G) study, which was designed to evaluate changes in and correlations between fatigue and cognition in natalizumab-treated patients with relapsing MS.…”
Section: Interventions and Assessmentsmentioning
confidence: 99%